1997
DOI: 10.1002/(sici)1097-0061(199708)13:10<931::aid-yea149>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Top- and Bottom-Fermenting Yeast

Abstract: The surface physico‐chemical properties (hydrophobicity, electrophoretic mobility, chemical composition) of a large set of top‐ and bottom‐fermenting brewing yeasts, harvested in the exponential and stationary growth phases, have been investigated. Bottom‐ and top‐fermenting strains showed different surface properties. Top strains were generally more hydrophobic than bottom strains, due to higher surface protein concentrations. Bottom strains possessed higher surface phosphate concentrations. The different pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The cell charge of brewing and the constitutively flocculent strains varied during the growth; however, no clear relationship among the CSC and the onset (or loss) of flocculation of the brewing strains was observed. These results are in agreement with other authors, which attribute a minor role of CSC on the onset of flocculation (Smit et al 1992;Dengis et al 1995;Dengis and Rouxhet 1997). Although it is described that ale (top) brewing fermentation strains are less negative charged than lager (bottom) strains Mestdagh et al 1990), no clear difference on the CSC was observed in the three strains used.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The cell charge of brewing and the constitutively flocculent strains varied during the growth; however, no clear relationship among the CSC and the onset (or loss) of flocculation of the brewing strains was observed. These results are in agreement with other authors, which attribute a minor role of CSC on the onset of flocculation (Smit et al 1992;Dengis et al 1995;Dengis and Rouxhet 1997). Although it is described that ale (top) brewing fermentation strains are less negative charged than lager (bottom) strains Mestdagh et al 1990), no clear difference on the CSC was observed in the three strains used.…”
Section: Discussionsupporting
confidence: 92%
“…It is conceivable that the reduction of global cell charge (non-specific electrostatic repulsion) should facilitate yeast cells approach; in this case, the macromolecules (lectins) present on yeast cell surface can easily overcome the negative barrier and the junction between lectins and carbohydrates (specific cell adhesion mechanism) is easier established. However, no clear relationship between yeast surface charge and the onset of flocculation was found Dengis et al 1995;Dengis and Rouxhet 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many yeast strains used in the brewing and wine industries form either flocs (e.g., bottom-fermenting yeasts used to make lagers) or flors (e.g., top-fermenting yeasts used to make sherry wines). In general, strains that form flors have higher surface hydrophobicity than those that form flocs (12). Unlike these industrial yeasts, most laboratory yeasts form neither flors nor flocs.…”
Section: Background (I) the Multifarious Yeast Communitymentioning
confidence: 99%
“…In dependency on the environmental conditions, these groups have an influence on the electrochemical charge of the cell wall [24,25]. Additionally the microbes produce extracellular polymeric substances (EPS) that may have an influence on the environmental conditions.…”
Section: Eps Analysismentioning
confidence: 99%